PERKEBUNAN KELAPA SAWIT INDONESIA DALAM PERSPEKTIF PEMBANGUNAN BERKELANJUTAN - Purba, Jan Horas V.; Sipayung, Tungkot (Masyarakat Indonesia, 2018)
The purpose of this study is to analyze (1) whether oil palm plantations are the main drivers of deforestation in Indonesia; and (2) how does the Indonesian palm oil industry contribute to sustainable development both economically, socially and ecologically. Oil palm plantations are Indonesia’s strategic industries. Since 2000, the Indonesian palm oil industry has grown rapidly and has influenced the dynamics of competition among vegetable oils including the form of black campaigns and accusations as drivers of deforestation in Indonesia. The research methodology is empirical descriptive research, which are: (1) to analyze the history of deforestation in logging era in Indonesia and related to the development of oil palm plantation and (2) to analyze the linkage of Indonesian oil palm plantation development with economic, social and ecological aspect. In the period 1950-2013, conversion of forests into non-forests is quite high ie 98.8 million hectares. However, the area of oil palm plantation Indonesia only increased from 0.1 million hectares (1950) to 10.4 million hectares (2013). Based on satellite data (Gunarso, et al., 2012) revealed that the origins of Indonesian oil palm plantations are mostly from degraded land, and only 3.4 percent are converted from primary forest. This proves that oil palm plantations as the main drivers of deforestation in Indonesia are not true. In the economic aspect, the palm oil industry contributes in generating foreign exchange, regional development and successfully creating farmers into middle income. In the social aspect, the oil industry plays a role in rural development and poverty reduction and equitable economic development, and improves income and development inequalities. In the ecological aspect, oil palm plantations contribute to sustainable development through its role in absorbing CO2 and generating O2, and increasing land biomass. Oil palm plantations also reduce greenhouse gas emissions.